ANALISIS SURVEI KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK DI RSUD KABUPATEN SAMPANG (Studi Deskriptif Di RSUD Kabupaten Sampang) - Enggal Sari Maduratna (DIA: Jurnal Administrasi Publik, 2016)
By looking at the increasing environmental demands on the quality of service, the necessary efforts to increase the quality of service by comparing the services expected by the service perceived by the public. Therefore, the government should take immediate measures of health care quality improvement efforts, so that the perceived benefits of the service as much as possible and improve the health of Indonesian society in general and especially for the people around the area Sampang. The research objective is to analyze the quality of services provided by hospitals to the community Sampang.This study didesaian descriptive quantitative with cross sectional approach. The object of research is based on the calculation Kep.MENPAN No. 25 in 2004 with the formula (number of elements + 1) x 10 = (160 + 1) x 10 = 170 respondents. Data collection tool using a questionnaire developed from PERMENPAN RB No. 16, 2014 consisting of 9 elements. Results obtained from 9 elements developed into 16 sub-indicators there are three elements that have unfavorable category. These three elements are the requirements, implementing procedures and behavior, which are then counted as a whole to look at the quality of service in get IKM value of 2.54 x 25 = 63.5 which can be categorized B (Good). From the analysis of researchers suggested the Sampang District Hospital to always make improvements, especially in the three elements considered less good, namely, requirements, procedures and executing behavior.Keywords: Public Satisfaction Survey, Public Services